ECONOMIC BOTANY: A BIBLIOMETRIC STUDY - Ch. Biswas, Bidhan; Roy, Amit; B.K., Sen (Malaysian Journal of Library and Information Science, 2017)
The study has been conducted with 358 original contributions published in the journal Economic Botany during 1994-2003. Contributions by single author and small teams comprising two or three authors account for about 80% of the papers. Among the citations, books accounted for 59%, and articles 41%. E citations started appearing from 1998 are still negligible in number. Charts, diagrams, photos and tables included in the articles total 396, 427, 859 and 925 respectively. The length of maximum number of articles (38%) ranges from six to 10 pages. Articles occupying 11 to 15 pages rank next accounting for 31%. The highest number of articles totaling 217 (60.61%) has emanated from academic institutions such as universities. The articles originate from 45 countries. The first four countries are responsible for 51.7%, the first ten countries for 67.8%, and the first 15 countries for 78.6% of the articles